2010
DOI: 10.1186/1477-7827-8-107
|View full text |Cite
|
Sign up to set email alerts
|

Administration of single-dose GnRH agonist in the luteal phase in ICSI cycles: a meta-analysis

Abstract: BackgroundThe effects of gonadotrophin-releasing hormone agonist (GnRH-a) administered in the luteal phase remains controversial. This meta-analysis aimed to evaluate the effect of the administration of a single-dose of GnRH-a in the luteal phase on ICSI clinical outcomes.MethodsThe research strategy included the online search of databases. Only randomized studies were included. The outcomes analyzed were implantation rate, clinical pregnancy rate (CPR) per transfer and ongoing pregnancy rate. The fixed effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 40 publications
2
42
0
4
Order By: Relevance
“…The possible mechanisms responsible for the effects of the GnRH agonist luteal action may be a direct beneficial effect on the embryos or uterine tissue. Nevertheless, it seems premature to recommend the use of the GnRH agonist in the luteal phase until further randomised controlled trials are provided [14].…”
Section: Dual Triggermentioning
confidence: 99%
“…The possible mechanisms responsible for the effects of the GnRH agonist luteal action may be a direct beneficial effect on the embryos or uterine tissue. Nevertheless, it seems premature to recommend the use of the GnRH agonist in the luteal phase until further randomised controlled trials are provided [14].…”
Section: Dual Triggermentioning
confidence: 99%
“…The use of triptorelin as luteal support allows sustaining constantly small flares of endogenous pituitary gonadotropins which can stimulate and recover the function of corpora lutea [18]. At the same time, the aggressive luteal support with triptorelin appears to have a direct effect on endometrium and embryo by acting on a placental GnRH receptor [19].…”
Section: Discussionmentioning
confidence: 99%
“…The use of triptorelin as luteal support allows sustaining constantly small flares of endogenous pituitary gonadotropins which can stimulate and recover the function of corpora lutea [18]. At the same time, the aggressive luteal support with triptorelin appears to have a direct effect on endometrium and embryo by acting on a placental GnRH receptor [19].In the group of patients included in our study, the choice of an intensive luteal support with progesterone plus triptorelin, instead of estrogens [20] or hCG [21], produced good effects.Our results are in line with previous data which demonstrated that repeated dose of a GnRH agonist during luteal phase recover the luteal phase deficiencyand is compatible with normal implantation and pregnancy evolution [22]. We also observed that three patients achieved pregnancy after the implantation of frozen-thawed blastocyst, and one patient achieved pregnancy after the transfer of vitrified oocytes, enhancing the pregnancy rate per stimulation.…”
mentioning
confidence: 99%
“…Usually GnRHa firstly induces an augmented pituitary response (flare up effect) followed by gradually pituitary down regulation [5,6]. There was successful report in animal study that taking advantage of the initial flare-up effect and using ultra-low dose of short-acting GnRHa to achieve multiple follicles development without exogenous gonadotropines, it suggested that GnRHa alone could generate enough FSH level and duration for multiple follicles recruitment [7].…”
Section: Discussionmentioning
confidence: 99%